Risk factors affecting cataract surgery outcome: The Malaysian cataract surgery registry. - Geng-Yi Yong; Jelinar Mohamed-Noor; Mohamad Aziz Salowi; Tassha Hilda Adnan; Mimiwati Zahari (PLoS ONE, 2022)
This is a 5 years multicentre database study that recruited subjects from the Malaysian Ministry of Health Cataract Surgery Registry (MOH CSR), aimed to determine risk factors that affect cataract surgery visual outcome and evaluates post-cataract surgery vision. All age-related cataract surgeries with primary intraocular lens (IOL) implantation were included. Cases with secondary cataract, previous ocular surgeries and incomplete data were excluded. A total of 131425 cases were included in the study. Amongst all types of cataract surgery, 92.9% attained post-operative best-corrected visual acuity better than 6/18 and the outcome improved to 97.1% when ocular comorbidities were excluded. Factors with Odds Ratio (OR) >1.5 associated with an impaired visual outcome included: elderly patients of 80 years old and above; systemic disease such as renal failure; ocular co-morbidities; pre-operative vision worse than 6/60; general anaesthesia, retrobulbar anaesthesia or subconjunctival anaesthesia; extracapsular cataract extraction (ECCE), intracapsular cataract extraction (ICCE), anterior chamber intraocular lens (ACIOL) implantation or combined cataract surgery; the presence of intra- and post-operative complications. In conclusion, a good visual outcome was achieved after cataract surgery in most cases. This large multicentre study provides information about risk factors for poor visual outcome post-cataract surgery and may serve as a basis for evidence-based guidelines.